2018
DOI: 10.1177/2167702618794923
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety and Social Behavior: A Test of Predictions From an Evolutionary Model

Abstract: developed an influential evolutionary model of social anxiety, tracing its origins to a phylogenetically old bias to conceptualize social interactions as competitive struggles in which key goals are to dominate or to avoid rejection or status loss. This bias makes sense in despotic nonhuman primate (NHP) species' social groups, which are organized around strict dominance hierarchies. In these NHP groups, social interactions frequently unfold in what the ethologist and pharmacologist Michael Chance (Chance, 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…However, the decision could be different if the customer possesses some personality traits, such as high tolerance level, faith on people, cooperative, optimistic, and forgiver nature. In addition, Tone et al (2019) found that specific personality traits are strongly associated to an individual's behavior. To this edge, in case of any negligence, a customer fully cooperates with a restaurateur and does not get disappointed immediately with the services (Thielmann et al, 2020).…”
Section: The Moderating Role Of Social Trustmentioning
confidence: 99%
“…However, the decision could be different if the customer possesses some personality traits, such as high tolerance level, faith on people, cooperative, optimistic, and forgiver nature. In addition, Tone et al (2019) found that specific personality traits are strongly associated to an individual's behavior. To this edge, in case of any negligence, a customer fully cooperates with a restaurateur and does not get disappointed immediately with the services (Thielmann et al, 2020).…”
Section: The Moderating Role Of Social Trustmentioning
confidence: 99%
“…For most primates, group cohesion is maintained by members recognizing and acting in accordance with their role in a social hierarchy (see Tone et al, 2019 for an overview). Two psychological systems govern this social order: social rank (a focus on power and dominance) and affiliation (a focus on reciprocity and intimacy).…”
Section: An Evolutionary Framework Of Social Comparisons In Social An...mentioning
confidence: 99%
“…Nevertheless, existing evolutionary theories of paranoia based solely on social threat detection do not fully account for the complex phenomenology of paranoia. Specifically, we have to ask why a mechanism aimed at detecting and avoiding social threats does not solely result in variation in avoidance, submissive or appeasement behaviours (as is also observed in many non-human species, see 54 and also discussed elsewhere 5559, but also incorporates more complex features that are not adequately explained by this approach. Namely, selective identification of a specific yet often seemingly arbitrary group of persecutors, the attribution of unobservable malign intentions and motives to these individuals, and the formulation of hypothetical narratives rendering these attributions subjectively plausible.…”
Section: Shortcomings Of Existing Evolutionary Theoriesmentioning
confidence: 99%